Jaminan Perlindungan Hukum Hak-Hak Guru Dengan Status Honorer Di Sekolah Negeri Kota Semarang - Rizkya Indah Permata Safitri; Sonhaji Sonhaji; Suhartoyo Suhartoyo (Law, Development and Justice Review, 2023)
Teachers are professional teachers who are a determining factor for the quality of nation. However, there are still problems regarding teachers, such as cases of teachers being reported to the authorities when carrying out their job, cases related to the lack of wages received, or cases of schools lacking the number of teachers. The existence of cases of teachers facing the law proves that legal arrangements and protection are needed, especially for honorary teachers who until now have not received clarity regarding their employment status. The purpose of this study is to determine the arrangement of honorary teachers and forms of legal protection guarantees for teachers with honorary status in public schools in the city of Semarang. This study uses empirical juridical research methods so that gaps can be found between existing rules and their implementation in society. The results of this study indicate that the form of guarantee of legal protection for teachers with honorary status is regulated by a work agreement and the implementation of legal protection arrangements for teachers with honorary status in Semarang City has been partially implemented according to the normative provisions set by the central government.